Clinical relevance of the modified physical performance test versus the short physical performance battery for detecting mobility impairments in older men with peripheral arterial disease. Issue 25 (4th December 2018) - Addison, Odessa; Kundi, Rishi; Ryan, Alice S.; Goldberg, Andrew P.; Patel, Richa; Lal, Brajesh K.; Prior, Steven J.
Abstract: Purpose: The study is to compare the Modified Physical Performance Test (MPPT) and Short Physical Performance Battery (SPPB) as metrics of mobility and function in older men with peripheral arterial disease (PAD). Materials and methods: A total of 51 men (55–87 years) with PAD underwent functional testing including the SPPB, MPPT, Walking Impairment Questionnaire (WIQ), stair ascent, and 6-min walk distance. Individuals were grouped according to SPPB and MPPT scores as not limited on either, limited only on the MPPT, or limited on both. Results: The MPPT identified a higher proportion of patients as being functionally limited than the SPPB ( p  < 0.001). Men identified as limited only by the MPPT, and not the SPPB, were subsequently confirmed to have lower function on all measures compared to those not identified as limited by either the SPPB or the MPPT ( p  < 0.02). Conclusions: These findings suggest the MPPT is an appropriate measure to identify early declines in men with PAD and may identify global disability better than SPPB. Implications for rehabilitation: Individuals with peripheral arterial disease have low activity levels and are at risk for a loss of independence and global disability. Early detection of decline in mobility and global function would allow for interventions before large changes in ambulatory ability or a loss of functional independence occur. This study shows the Modified Physical Performance Test may be an appropriate test to identify early decline in function in men with peripheral arterial disease.